1998
DOI: 10.1046/j.1420-9101.1998.11060755.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary genetics and ecology of sperm‐dependent parthenogenesis

Abstract: Sperm-dependent (or pseudogamous) forms of parthenogenetic reproduction occur in a wide variety of animals. Inheritance is typically clonal and matroclinous (of female descent), but sperm are needed to initiate normal development. As opposed to true parthenogenesis (i.e., sperm-independent reproduction), pseudogamous parthenogenetic lineages must coexist with a 'sperm donor' ~ e.g., males from a conspecific sexual lineage, conspecific hermaphrodites, or males from a closely related sexual species. Such sperm d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
130
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(132 citation statements)
references
References 113 publications
1
130
1
Order By: Relevance
“…It has been reported that gynogenetically reproducing animals have evolved unusual mechanisms to maintain the chromosome ploidy: The maturation division does not proceed through "normal meiosis" but with considerable deviations (Beukeboom and Vrijenhoek, 1998). The gibel carp also shows deviations in maturation division during gametogenesis (Din and Jiang, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that gynogenetically reproducing animals have evolved unusual mechanisms to maintain the chromosome ploidy: The maturation division does not proceed through "normal meiosis" but with considerable deviations (Beukeboom and Vrijenhoek, 1998). The gibel carp also shows deviations in maturation division during gametogenesis (Din and Jiang, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…In general, bisexually reproducing animals are functionally diploid and contain two chromosome sets that undergo meiotic synapsis and segregation. The other is gynogenetic reproduction, a type of sperm-dependent parthenogenesis, where the sperm is necessary only for activating the egg but does not contribute its nucleus to the next generation (Beukeboom and Vrijenhoek, 1998). Gynogenesis is not present in mammals and birds but is common in invertebrates and lower vertebrates such as reptiles, amphibians, and fish.…”
Section: Introductionmentioning
confidence: 99%
“…In the present paper, we performed sibship analyses with 15 co-dominant microsatellite loci to evaluate genome-wide clonal (males absent), restricted to reptiles [7,8]; Sperm-dependent parthenogenesis (i.e. gynogenesis): clonal, embryogenesis requires trigger from allospecific sperm that is not incorporated (rare 'paternal leakage' might incorporate subgenomic amounts of paternal DNA), occurs in teleost fishes and urodelan amphibians [9]; Kleptogenesis: females acquire full or partial genomes from their mates by a not fully understood mechanism, allowing them to purge genomes from deleterious alleles (here BB); described from urodelan amphibians [10]; Unnamed form of hybridogenesis: clonal diploid eggs are fertilized by sperm from a recombining sexual species that can be diploid or triploid (as in meiotic hybridogenesis); occurs in anuran amphibians and teleost fishes [11][12][13]; Meiotic hybridogenesis: may occur in triploid males and/or females; found in teleost fishes and anuran amphibians [14,15]; ploidy elevation of the diploid offspring, which might produce diploid hybrid gametes, can occur in the next generation (becoming then e.g. ABB 0 ) to restore triploidy (similar to preceding form of hybridogenesis); Pre-equalizing hybrid meiosis: occurring in Batura toads: Both sexes are triploid and exhibit Mendelian segregation and recombination in the B genomes (equivalent to NORþ; this paper), while the A genome (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Although not a common mode of reproduction, sperm-dependent parthenogenesis has evolved multiple times within seven phyla (Beukeboom and Vrijenhoek, 1998). It may simply be considered as an evolutionary transition towards obligate parthenogenesis, but it has also been questioned whether such a reproduction mode would confer any selective advantage.…”
mentioning
confidence: 99%